Strategic approach to improve customer awareness of heritage bazaar at Dataran Pahlawan, Bandar Hilir Melaka - Case MBMB / Siti Aisyah Abd Sukor - Abd Sukor, Siti Aisyah (Faculty of Business and Management, 2007)
A bazaar is a permanent merchandising area, marketplace, or street of shops where goods and services are exchanged or sold. The word derives from the Persian word bazar, the etymology of which goes back to the Pahlavi word baha-char meaning "the place of prices". Although the current meaning of the word is believed to have originated in Persia, its use has spread and now has been accepted into the vernacular in countries around the world. Heritage Bazaar is one of the popular places in Malacca. Heritage Bazaar provides tourist variety of souvenir, traditional food and also creative handicraft. This bazaar is located nearby the historical places such as 'Independence of Memorial, 'Light and Sound', 'Bangunan Merah' and other interesting historical places. This bazaar located at Jalan Taman in Bandar Hilir. They are operated more than 10 years and still operating until now. They run their business in group in certain places but still in Bandar Hilir.